Proces rozszerzenia NATO jako instrument realizacji polskiej polityki wschodniej. Nowe uwarunkowania geostrategiczne - Drzewicki, Artur (Instytut Studiów Międzynarodowych Uniwersytetu Wrocławskiego, 2013)
Author assesses the significance of the principle of NATO expansion in the process of molding and realization of guidelines of Polish eastern policy. Considering the idea of “open doors” lately one of the main instruments of Poland’s political influence on the states of the post-Soviet area, author arrives at a conclusion, that in present-day geostrategic circumstances it has lost its significance and ceased to be a real instrument of shaping of polish eastern policy. However, this does not mean that it shouldn’t be taken into consideration in the process of creation of new conceptions concerning future of East European countries, including, first of all, Ukraine.
Keywords: Kościół katolicki; polityka wschodnia; Ukraina; Federacja Rosyjska; Unia Europejska; NATO; relacje polsko-ukraińskie; stosunki polsko-rosyjskie; kościół prawosławny; dyplomacja publiczna; bezpieczeństwo